Tracing timber origin: Geographic provenancing at regional scale with multielement and strontium isotope ratio analyses - Aguzzoni, Agnese; Giammarchi, Francesco; Mundo, Ignacio A.; Voto, Giulio; Tonon, Giustino; Tirler, Werner; Tomelleri, Enrico (Forest ecology and management, 2025)
International timber trading is subject to rigorous certification schemes that require the disclosure of essential information, including the tree species and geographic origin of the timber in question. Regrettably, the lack of readily accessible forensic tools to verify compliance has facilitated the proliferation of illegal timber trading, with dramatic consequences for ecosystems and biodiversity. The objective of this study was to investigate the potential of a multichemical approach based on the multielement and strontium isotope (87Sr/86Sr) ratio analysis combined with chemometrics to test sample recognition according to their species and geographic origin. The sampling area covered a regional-scale portion of the Eastern Alpine region (< 30 000 km2), for highlighting the applicability of the approach within a spatially constrained context. The study focused on three representative species from local forests: Norway spruce, European larch, and Swiss stone pine. Samples were characterised from stands grown on diverse bedrock types. Our findings revealed a strikingly consistent variation in the multielement profiles across different species, thereby enabling flawless sample recognition. Considering the geographic origin, the 87Sr/86Sr ratio proved to be a pivotal parameter, by virtue of its correlation with the geo-lithological composition of the growing area. Combining the chemical markers, an accurate sample classification based on multiple decision trees was attained, even comparing forest stands grown on the same bedrock type. These findings offer novel insights into the utilisation of chemical markers in provenancing and authenticity studies, thereby enhancing the adoption of integrated approaches to counteract illegal timber trade. [Display omitted] •Timber compliance verification requires scientific supporting evidence.•A multichemical approach was tested to classify wood samples from the Alpine region.•The multielement fingerprint identified uniquely sample species.•The strontium isotope ratio confirmed to be an excellent origin marker.•Chemical markers are a robust tracking method for forensic timber identification.